2013
DOI: 10.1371/journal.pone.0063639
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Chytridiomycosis in European Plethodontid Salamanders of the Genus Speleomantes

Abstract: North America and the neotropics harbor nearly all species of plethodontid salamanders. In contrast, this family of caudate amphibians is represented in Europe and Asia by two genera, Speleomantes and Karsenia, which are confined to small geographic ranges. Compared to neotropical and North American plethodontids, mortality attributed to chytridiomycosis caused by Batrachochytrium dendrobatidis (Bd) has not been reported for European plethodontids, despite the established presence of Bd in their geographic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…European amphibians have heterogeneous responses to Bd exposure. Some species are susceptible to both infection and mortality attributable to chytridiomycosis, others seem less likely to suffer from either, and still others are refractory to infection (Pasmans et al 2013). At present, Bd is widespread across Europe, where the general pattern appears to be a coexistence steady state within amphibian communities (Balá et al 2014;Spitzen-van der Sluijs et al 2014).…”
Section: Chytridiomycosis By An Martel and Frank Pasmansmentioning
confidence: 98%
“…European amphibians have heterogeneous responses to Bd exposure. Some species are susceptible to both infection and mortality attributable to chytridiomycosis, others seem less likely to suffer from either, and still others are refractory to infection (Pasmans et al 2013). At present, Bd is widespread across Europe, where the general pattern appears to be a coexistence steady state within amphibian communities (Balá et al 2014;Spitzen-van der Sluijs et al 2014).…”
Section: Chytridiomycosis By An Martel and Frank Pasmansmentioning
confidence: 98%
“…Unlike for anurans, information about the AMP arsenal in skin secretions of urodelans is scant. In several salamanders species, the antimicrobial action of skin secretions has been attributed to antimicrobial compounds, most probably including AMPs [ 90 , 91 ]. However, to date only a single antimicrobial peptide (the defensin CFBD) has been described from Cynops fudingensis (Fuding fire belly newt) [ 92 ], leaving a wealth of novel AMPs to be discovered.…”
Section: Pathogenesismentioning
confidence: 99%
“…To our knowledge, the antimicrobial action of CFBD against both Batrachochytrium species has not (yet) been evaluated. Although published data are virtually lacking, AMPs may be involved in the anti- B. dendrobatidis activity of salamander skin secretions [ 90 , 91 ] and potentially play a role in defense against B. salamandrivorans .…”
Section: Pathogenesismentioning
confidence: 99%
“…For more information on the environmental impact of hostpathogen interactions, which can be hugely deterministic in some cases, see Blaustein et al (2018) for an in-depth discussion. Experiments have also shown that some salamanders such as those in the genus Speleomantes also have some immunity to Bd (Pasmans et al, 2013). This combined effect of peptide defence and varying Bd strains show that at least for now, some species of European amphibians are protected against the potentially negative effects of Bd outbreaks (Fisher et al, 2009).…”
Section: Emerging Infectious Disease Threats To Amphibians Batrachochmentioning
confidence: 99%